Postmenopausal spontaneous rupture of pyometra - Verma, Aruna; Maheshwari, Raghavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Spontaneous perforation of pyometra resulting in generalized diffuse peritonitis is extremely uncommon, ranging from 0.01% to 0.5%. Herein, we report the case of a 55 year old postmenopausal woman, presented with acute abdominal pain, distended abdomen, and inability to pass flatus and feces, and purulent vaginal discharge. In view of generalized peritonitis, laparotomy was performed on which 3000 cc pus was suctioned out and necrotic tissue was found on the surface of liver and intestines. The uterus was found to have a 2×2 cm sized perforation at fundo-posterior surface from which purulent material was seen exuding. Thus, a diagnosis of perforated uterus due to pyometra was made. A total abdominal hysterectomy with bilateral salpingo-oophorectomy with thorough peritoneal lavage was done. Histopathological examination revealed perforated uterus with pyometra, but there was no evidence of malignancy, and the cervical canal was patent. The patient had burst abdomen on 6th postoperative day and subsequent resuturing was done. She was discharged on 17th postoperative day in satisfactory condition. Thus, rarely, perforation of uterus due to pyometra can cause peritonitis in postmenopausal females with signs of acute abdomen.